2014
DOI: 10.1097/aog.0000000000000018
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Topiramate and Zonisamide Use During Pregnancy and Low Birth Weight

Abstract: II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(41 citation statements)
references
References 22 publications
1
39
0
1
Order By: Relevance
“…The Australian pregnancy register reported a particularly high rate of MCMs for TPM when used as polytherapy, at 14.1 % with a relative risk of 4.32 (95 % CI 1.57-11.05) compared with no AED exposure [13]. Another major concern is a high rate of small for gestational age (SGA) births following in utero exposure to TPM; the NAAPR reported that 17.9 % of TPMexposed infants were SGA with a relative risk of 2.4 (95 % CI 1.8-22) compared with LTG [14]. In 2011, the Food and Drug Administration made a label change, from a Pregnancy Category C to D, based on these reports [15].…”
Section: Tpmmentioning
confidence: 99%
See 1 more Smart Citation
“…The Australian pregnancy register reported a particularly high rate of MCMs for TPM when used as polytherapy, at 14.1 % with a relative risk of 4.32 (95 % CI 1.57-11.05) compared with no AED exposure [13]. Another major concern is a high rate of small for gestational age (SGA) births following in utero exposure to TPM; the NAAPR reported that 17.9 % of TPMexposed infants were SGA with a relative risk of 2.4 (95 % CI 1.8-22) compared with LTG [14]. In 2011, the Food and Drug Administration made a label change, from a Pregnancy Category C to D, based on these reports [15].…”
Section: Tpmmentioning
confidence: 99%
“…Findings from the 2009 AAN/AES practice parameter Update [1] concluded the following : neonates of WWE taking AEDs probably have an increased risk of being SGA of about twice the expected rate. In addition to TPM, elevated prevalence of SGA births has been reported with zonisamide, VPA, and CBZ [14,19]. A retrospective, cross-sectional study utilizing 2 nationwide population-based data sets reported increased ORs (1.3-1.6) for SGA, low birth weight, and preterm deliveries in women who had seizures during pregnancy compared with women without epilepsy, and the risk of SGA births was still increased when compared with WWE who were seizure-free during pregnancy (OR 1.34; 95 % CI 1.01-1.84).…”
Section: Neonatal and Obstetric Complicationsmentioning
confidence: 99%
“…61 In 2014, the registry also reported an increase in the incidence of low birth weight among infants exposed to TPM in utero (17.9%) compared with controls (5.0%). 62 When compared with lamotrigine-exposed babies, TPM-exposed babies had a 221 g decreased birth weight with a 1 cm decreased mean length. 62 This effect appeared to persist despite adjusting for factors such as age, parity, smoking, education, and folic acid intake.…”
Section: Use In Pregnancymentioning
confidence: 99%
“…62 When compared with lamotrigine-exposed babies, TPM-exposed babies had a 221 g decreased birth weight with a 1 cm decreased mean length. 62 This effect appeared to persist despite adjusting for factors such as age, parity, smoking, education, and folic acid intake. The serum concentrations of TPM appear to decline gradually during pregnancy.…”
Section: Use In Pregnancymentioning
confidence: 99%
“…1,18,25 Topiramate has been associated with increased risk of cleft abnormalities, as well as low birth weights and small for gestational age infants. 1,25,27 Emerging data on newer AEDs as monotherapy have demonstrated the relative safety of levetiracetam, 19,28 lamotrigine, 19 oxcarbazepine, and zonisamide 29 in WWE who are pregnant; however, data are more limited for the latter two. Levetiracetam and lamotrigine in particular have not been associated with increased risk of MCM compared to controls and are generally considered safe to use in pregnancy.…”
mentioning
confidence: 99%